Questioning of Saul's Nudity Before Samuel in 1 Samuel 19:24 - Vena Melinda Tiladuru (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
Saul's nakedness before Samuel was the removal of the outer robe or robe of government. Saul himself was still wearing a tunic that was also worn by ordinary people, this was a reaction when the Spirit of God came upon him. This exploration of the meaning of Saul's nudity uses a descriptive biblical qualitative research with the hermeneutic principle of analyzing the meaning of the word naked. The results of this study indicate that the meaning of Saul's nudity (robe calendar); first, it was a sign that his reign was coming to an end. Second, it was the last time when Samuel would no longer talk to him and the Spirit of God left him.